The Harmonization of Authority of Supreme Court, Constitution Court, and the Judicial Commission - La Ode Angga La Ode Angga (Fiat Justisia: Jurnal Ilmu Hukum, 2018)
The Harmonization of the Authority between Supreme Court (MA) institutions The Constitutional Court (MK) and Judicial Commission (KY) is a must. It is done by way of revision of the Law of the Supreme Court, MK and KY for the harmonization of authority. However, if the revision finds a dead end, then the fifth amendment (5) of the 1945 Constitution of the State of the Republic of Indonesia (UUDNRI 1945) is limited to be reconstructed by the provision of Article 24B paragraph (1) of the 1945 Constitution by affirming the authority of KY clear so that it is not considered to interfere with judicial power. The harmonization can be done by adding an institution that oversees the authority of the Constitutional Court by performing reconstruction in Article 24B paragraph (1) so that there is no more tendency of absolute power. The supervised judge is a judge of the Supreme Court and the Constitutional Court.  Keywords: Harmonization, Authority, Supreme Court, Constitutional Court, Judicial Commission.